Cana-de-açúcar irrigada com águas de diferentes níveis de salinidade e lâminas de lixiviação : respostas fisiológicas e bioquímicas - GODOI NETO, Anízio Honorato (2018)
The objective of this study was to evaluate the effect of irrigation water salinity and leaching fractions on sugarcane cultivation, investigating the physiological and biochemical aspects of the plants. The experiment was conducted at the Department of Agricultural Engineering (DEAGRI), Federal Rural University of Pernambuco (UFRPE), Campus Recife. A completely randomized design was used in a 5 x 2 factorial arrangement, with 4 replications. Five irrigation water salinity levels were used with two leaching fractions (0 and 0.17) corresponding to 100% and 120% of crop evapotranspiration. The salinity levels used were: 0.5; 2.0; 4.0; 6.0 and 8.0 dS m-1, being reached by addition of NaCl and CaCl2 to the local supply water (0.5 dS m-1). The sugarcane variety RB 92579, cultivated in drainage lysimeters, was used. At 60 days after planting (DAP) the application of the treatments through drip irrigation was started. The physiological responses of the plants were performed at 90, 150 and 210 DAS with the infrared gas analyzer (IRGA LI-6400), in which the following variables were determined: photosynthesis (A), stomatal conductance (gsw), transpiration (E), intercellular CO2 (C 1), foliar temperature (TLeaf), instantaneous water use efficiency (A / E), intrinsic water use efficiency (A / gsw), instantaneous carboxylation efficiency ratio of intercellular CO2 concentration in the mesophyll and external CO2 concentration (Ci / Ca), in a +3 leaf of a plant per treatment. A +3 leaf was collected for analyzes of the enzymatic activity of catalase (CAT) and ascorbate peroxidase (APX). The samples were collected at 90, 150, 210 and 270 days after planting. sol the water potential with the aid of a Scholander chamber using a +3 sheet. The water potential presented a quadratic reduction as the salt levels increased, and the enzymatic behavior increased as the accumulation of salts in lysimeters increased to 6.98 dS m-1 for CAT and 7.27 dS m-1 for APX. For the gas exchanges (A, E, gsw and Ci) presented a linear reduction as the salt levels increased, already the temperature showed an increase of 2 ° C. The photosynthetic pigments (chlorophyll a, b and carotenoids) showed a reduction in their quantity as salt levels increased, demonstrating that saline stress interferes with the synthesis and degradation of the pigments. The leaching fraction presented better efficiency when compared to 100% ETc, promoting a greater increase in the analyzed variables.